Development of website related to badminton - Yam, Ching Hann (2022)

(untitled)
Despite the government’s announcement that all businesses can operate as normal, the government still encourages people and businesses to strictly follow SOP policies to prevent the spread of the virus and reduce the number of confirmed cases. However, it is still a disadvantage for traditional badminton stores because customers need to strictly abide by the SOP policy which they may not be able to view the badminton products, unable to purchase easily and can only attract customers who visit their stores. Besides, many badmintons societies lack online platforms to post their events and watch events (and news) posted by others. Therefore, this project titled “Development of Website Related to Badminton”, is being developed to create an effective and user-friendly online badminton website by providing a racket recommendation function to propose a few suitable rackets to customers according to their condition. The website not only provides shopping functions such as browsing products, adding them to the cart, and making checkout, but it also allows users to view recent news about badminton and be able to post badminton events on the website. For the admin part, the admin is able to view and manage products and manage the posting events by user. The project is carried out using the RAD (Rapid Application Development) methodology and consists of 4 phases: requirement planning, user design, rapid construction, and cutover. The front-end development of this project is mostly done with HTML, CSS, JavaScript, and jQuery, while the server-side development is done with PHP and MySQL.